Organizational identification and member retention in nonprofit organizations: communication and accountability - María Alejandra Osorio Arias; Zuray Melgarejo Molina; Katrin Simon Elorz (Tendencias)
Introduction: Nonprofit Organizations (NPOs) face a complex relationship with their stakeholders. For their performance to be successful, it is crucial to implement strategies that link the social value of their mission to their management, enhancing their legitimacy without compromising operational efficiency. Objective: The purpose of this study is to identify the communication factors used by NPOs in their accountability processes that generate identification and retention of members in the Asociación Colombiana de las Micro, Pequeñas y Medianas Empresas [Colombian Association of Micro, Small, and Medium Enterprises] (ACOPI) Bogotá – Cundinamarca from 2016 to 2020. Methodology: A qualitative approach was adopted, with descriptive and interpretive scope, based on interviews with members of the Board of Directors and staff of ACOPI. Results: The organization has developed an effective strategic communication approach that favors member retention, brand positioning, and the fulfillment of its mission, using both interactive and traditional communication channels. Members show strong emotional and behavioral attachment, which reinforces their identification with and commitment to the association. Conclusion: The analysis revealed that fulfilling the mission improves organizational performance and strengthens members’ trust.